1998
DOI: 10.1074/jbc.273.33.21105
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiple PDZ Domain-containing Molecule Interacting withN-Methyl-d-aspartateReceptors and Neuronal Cell Adhesion Proteins

Abstract: At synaptic junctions, pre-and postsynaptic membranes are connected by cell adhesion and have distinct structures for specialized functions. The presynaptic membranes have a machinery for fast neurotransmitter release, and the postsynaptic membranes have clusters of neurotransmitter receptors. The molecular mechanism of the assembly of synaptic junctions is not yet clear. Pioneering studies identified postsynaptic density (PSD)-95/SAP90 as a prototypic synaptic scaffolding protein to maintain the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
286
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 278 publications
(294 citation statements)
references
References 44 publications
(59 reference statements)
7
286
0
1
Order By: Relevance
“…MAGI1 localizes to cell-cell contacts and acts as a scaffold molecule to stabilize cadherin-mediated adhesions and to recruit molecules at cell-cell contacts in endothelial and epithelial cells (Laura et al, 2002). Through its PDZ domains MAGI1 associates with a variety of PDZ-binding molecules such as N-methyl-Daspartate receptors (Hirao et al, 1998), d-catenin (Ide et al, 1999), brain specific angiogenesis inhibitor 1 (BAI-1) (Mino et al, 2000), mNET1 (Dobrosotskaya, 2001), phosphatase and tensin homologue (PTEN) (Kotelevets et al, 2005) and b-catenin (Dobrosotskaya and James, 2000;Kawajiri et al, 2000). In epithelial cells MAGI1 localizes at adherens junctions in complex with b-catenin/ E-cadherin (Dobrosotskaya and James, 2000;Kawajiri et al, 2000) as well as at tight junctions (Ide et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…MAGI1 localizes to cell-cell contacts and acts as a scaffold molecule to stabilize cadherin-mediated adhesions and to recruit molecules at cell-cell contacts in endothelial and epithelial cells (Laura et al, 2002). Through its PDZ domains MAGI1 associates with a variety of PDZ-binding molecules such as N-methyl-Daspartate receptors (Hirao et al, 1998), d-catenin (Ide et al, 1999), brain specific angiogenesis inhibitor 1 (BAI-1) (Mino et al, 2000), mNET1 (Dobrosotskaya, 2001), phosphatase and tensin homologue (PTEN) (Kotelevets et al, 2005) and b-catenin (Dobrosotskaya and James, 2000;Kawajiri et al, 2000). In epithelial cells MAGI1 localizes at adherens junctions in complex with b-catenin/ E-cadherin (Dobrosotskaya and James, 2000;Kawajiri et al, 2000) as well as at tight junctions (Ide et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic scaffolding molecule (S-SCAM) was originally identified as a SAPAP-interacting protein (24). We have first reported that S-SCAM has one GK, two WW, and five PDZ domains (24). The GK domain of S-SCAM is shorter than that of PSD-95/SAP90.…”
mentioning
confidence: 99%
“…The ligands for other PDZ domains of glutamate receptor-interacting protein have not been so far reported. Synaptic scaffolding molecule (S-SCAM) was originally identified as a SAPAP-interacting protein (24). We have first reported that S-SCAM has one GK, two WW, and five PDZ domains (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…pCMV NMDAR1, pCMV NMDAR2A, and pCMV SAPAP1 were as previously described Hirao et al 1998). The eukaryotic expression constructs of SAPAP are summarized in Fig.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%